E pluribus unum and civil harmony at election time. Issue 3 (10th July 2020) - Peters, Ted
Abstract: One way to formulate the task of the public theologian at election time is to interpret America's motto, e pluribus unum (out of many, one). Civility both presumes oneness while promoting oneness. After four years of ceaseless divisiveness from the White House, America needs political leadership that promotes a sense of belonging that includes persons of all races, ethnicities, economic classes, ages, genders, and country of origin. The public theologian combats xenophobia and the fear of replacement by demanding police reform, establishing a comprehensive national health delivery system, and comforting those who are anxious about their future in the unum .